A Novel Sintered Stainless Steel Fiber Felt with Rough Surface Morphologies. (13th November 2014) - Fang, Chaobin; Wan, Zhenping; Liu, Bin; Lu, Longsheng
Abstract : A novel sintered stainless steel fiber felt (SSSFF) with rough surface morphologies and high strength as well as high porosity is fabricated by solid-state sintering of stainless steel fibers produced by cutting method. The rough surface morphologies are characterized by laminar and jagged structures formed on the surface of stainless steel fibers. The SSSFF with 85% porosity sintered at 1200°C for 60 min exhibits tensile strength of 19 MPa and yield stress of 10.5 MPa. The influence of sintering parameters on surface morphologies and tensile strength is investigated. The experimental results show that the rough surface structures will disappear gradually when sintering temperature is 1300°C or sintering time is excessive, that is, 240 min when sintering temperature is 1200°C. The SSSFF with high porosity presents high tensile strength when sintering temperature ranges from 1100°C to 1200°C and sintering time is from 60 min to 120 min. In addition, the fracture mechanism of the SSSFF is investigated when subjected to uniaxial tensile load.